PENINGKATAN KESADARAN METAKOGNITIF DAN HASIL BELAJAR MELALUI PENERAPAN MODEL DISCOVERY LEARNING PADA PEMBELAJARAN IPS - Sri Hastati; Erwin Nurdiasyah (STKIP Andi Matappa Pangkep, 2019)
This study aims to determine (i) increasing metacognitive awareness and learning outcomes through the application of discovery learning models in IPS learning in class v sdn no. 79 sawakong towa takalar. Types of classroom action research. The focus of research is teacher and student factors, metacognitive awareness, and learning outcomes. The subjects of this study were fifth grade students at SDN No. 79 Sawakong Towa Takalar with 27 students in the 2019/2020 school year. Data collection techniques were observation, tests, questionnaires and documentation. Data analysis techniques are quantitative and qualitative analysis. Based on the results of research the actions taken by researchers in class V SDN No. 79 Sawakong Towa Takalar, it can be concluded that the implementation of the discovery learning model is one of the learning models that can be applied to increase the metacognitive awareness of students so that students are encouraged to think of good ways of learning to do. By implementing the discovery learning model the activity and student learning outcomes significantly increased in social studies learning in class V SDN No. 79 Sawakong Towa Takalar. Each cycle has increased and in the learning process students gain meaningful knowledge.